Optimal Design of the Leaching Stage in the Manufacturing Process of Surimi Gel - Reinheimer, Maria Agustina (2013)
The leaching stage in the manufacturing process of surimi gel requires a large amount of wash water contributing to a high operating cost. Therefore, the minimization of the wash water demand is essential for a low cost operation. In this paper, a complete mathematical model for the simultaneous optimization of the process configuration and the operating conditions of the continuous leaching process is presented. A superstructure formulation that embeds not only known process arrangements for the leaching process but also hybrid configurations is proposed. It is modeled as a nonlinear programming mathematical model. Given the design goal (extraction rate), the aim is to obtain the best process arrangement and operating conditions at minimum wash water demand. An interesting result obtained from the superstructure optimization is that, for a given extraction yield of soluble protein and total volume of leaching tank, the same minimum fresh water requirement is obtained with different leaching arrangements and with different distributions of flow rates. In addition, a sensitivity analysis was conducted in order to study the influence of the total volume of leaching tanks, number of leaching cycles, and extraction yield of soluble protein on the minimum fresh water consumption (countercurrent arrangement). As expected, for a given percentage of extraction from soluble proteins, the fresh water consumption significantly decreases, following an exponential decay law, as the total volume increases. A sensitivity analysis reveals that the minimum theoretical water consumption is obtained for four or higher number of washing cycles.